2017
DOI: 10.1136/thoraxjnl-2016-209753
|View full text |Cite
|
Sign up to set email alerts
|

‘WNT-er is coming’: WNT signalling in chronic lung diseases

Abstract: Chronic lung diseases represent a major public health problem with only limited therapeutic options. An important unmet need is to identify compounds and drugs that target key molecular pathways involved in the pathogenesis of chronic lung diseases. Over the last decade, there has been extensive interest in investigating Wingless/integrase-1 (WNT) signalling pathways; and WNT signal alterations have been linked to pulmonary disease pathogenesis and progression. Here, we comprehensively review the cumulative ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
138
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 134 publications
4
138
0
5
Order By: Relevance
“…Although IPF, asthma, and COPD are characterized by distinct etiology and pathology, these chronic lung diseases exhibit a shared airway epithelial phenotype, increased mucus cell frequency, decreased ciliated cell frequency, and increased WNT/β‐catenin signaling. To date, a cause and consequence relationship between increased WNT/β‐catenin signaling and changes in cell type frequency has not been previously demonstrated . This study indicates that interactions between β‐catenin and P300 or CBP vary under conditions where β‐catenin levels can fluctuate (normal) or are constantly high (disease).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Although IPF, asthma, and COPD are characterized by distinct etiology and pathology, these chronic lung diseases exhibit a shared airway epithelial phenotype, increased mucus cell frequency, decreased ciliated cell frequency, and increased WNT/β‐catenin signaling. To date, a cause and consequence relationship between increased WNT/β‐catenin signaling and changes in cell type frequency has not been previously demonstrated . This study indicates that interactions between β‐catenin and P300 or CBP vary under conditions where β‐catenin levels can fluctuate (normal) or are constantly high (disease).…”
Section: Resultsmentioning
confidence: 71%
“…An expanding body of literature indicates that the wingless/integrase-1 (WNT)/β-catenin pathway (see below) is activated in these chronic lung diseases and results in persistent β-catenin-dependent gene expression (reviewed in ref. [7]). However, the relationship between WNT/β-catenin pathway activity and changes in differentiated cell frequency is unknown.…”
Section: Airway Pathology In Chronic Lung Diseasementioning
confidence: 99%
“…Chronic epithelial injury and subsequent hyperplasia of ATII cells with the release of growth factors and cytokines are key features of IPF that contribute to distorted epithelial‐mesenchymal crosstalk and (myo)fibroblast function. Several signaling pathways have been demonstrated to be involved in fibrogenesis, among them are the TGF‐β and WNT/β‐catenin pathways (5). Here, we observed that both, TGF‐β and WNT/β‐catenin activation induce RUNX2 expression, which is in line with previous reports that reported RUNX2 to be a WNT/β‐catenin target gene in osteoblastic cells or mammary epithelium (18, 39).…”
Section: Discussionmentioning
confidence: 99%
“…These myofibroblasts form so‐called fibroblastic foci with increased deposition of extracellular matrix (ECM) (3). It has been demonstrated that disturbed epithelial–mesenchymal crosstalk is driven via epithelial secretion of different growth factors, such as TGF‐β and PDGF, as well as via the reactivation of developmental pathways, such as WNT, sonic hedgehog, or Notch (3, 5). Although two drugs have recently been approved for therapy, the prognosis of IPF remains poor.…”
mentioning
confidence: 99%
“…Upon binding to various transmembrane receptors, the different WNT ligands can induce two different responses: either activating the β-catenin dependent (canonical) or β-catenin independent (non-canonical) signaling pathways [reviewed in (5)]. In a recent study, Baarsma et al observed a transition from canonical to noncanonical WNT signaling during the development of COPD (6).…”
mentioning
confidence: 99%